2004
DOI: 10.1002/cyto.a.20087
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and validation of confocal spectral imaging systems

Abstract: Background: Confocal spectral imaging (CSI) microscopic systems currently on the market delineate multiple fluorescent proteins, labels, or dyes within biological specimens by performing spectral characterizations. However, some CSI systems have been found to present inconsistent spectral profiles of reference spectra within a particular system and between related and unrelated instruments. This variability confirms that there is a need for a standardized, objective calibration and validation protocol. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 19 publications
2
85
0
Order By: Relevance
“…The pinhole aperture was opened in this protocol because we needed to maximize signal to noise by collecting thicker optical sections. As previous comprehensive studies have shown, the pinhole size clearly affects the spectral performance; therefore, all experiments were conducted in the exact same conditions (22,23). Our reflection/mirror standard of a chromium-coated coverslip allowed us to operate the CLSM intact using the illumination sources required for the fluorescence excitation of our fluorophores.…”
Section: Live Cell Spectral Analysis Of Draq5 and The Impact Of Cell mentioning
confidence: 99%
“…The pinhole aperture was opened in this protocol because we needed to maximize signal to noise by collecting thicker optical sections. As previous comprehensive studies have shown, the pinhole size clearly affects the spectral performance; therefore, all experiments were conducted in the exact same conditions (22,23). Our reflection/mirror standard of a chromium-coated coverslip allowed us to operate the CLSM intact using the illumination sources required for the fluorescence excitation of our fluorophores.…”
Section: Live Cell Spectral Analysis Of Draq5 and The Impact Of Cell mentioning
confidence: 99%
“…Additional factors for good images include the optimization of the confocal operational variables (i.e. objective lens, averaging, pinhole size, bleaching, PMT voltage, laser excitation source, and spectral registration) of the confocal microscope and checking the CLSM to insure proper performance (36,37,(39)(40)(41)(42). We were able to effectively combine the spectra from two probes LT and AIF, which had different spectra, into an image that contained a specific probe (LT) for functional activity and a probe (AIF) to identify ovarian morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the size of the follicles, the following objectives were used: Leica Plan Apo 103 (0.4 NA) and Leica Plan Apo 203 (0.7 NA). A series of confocal microscopy performance tests were used to ensure that the confocal microscope was working correctly (36,37,(39)(40)(41)(42). A triple dichroic (TD) excitation filter was used for morphology and a 70/30 reflection dichroic was used for spectral analysis.…”
Section: Leica Tcs-sp1 Confocal Microscopementioning
confidence: 99%
See 2 more Smart Citations